Decarbonization of China's electricity systems with hydropower penetration and pumped-hydro storage: Comparing the policies with a techno-economic analysis. (August 2022) - Wang, Xiaokui; Bamisile, Olusola; Chen, Shuheng; Xu, Xiao; Luo, Shihua; Huang, Qi; Hu, Weihao
Abstract: Hydropower has a key role to play in achieving carbon neutrality targets. However, the rapid development of hydropower plants and the slowdown in the growth of electricity demand can easily cause imbalances in the energy system. Therefore, this study explores the possibility of achieving deep decarbonization by 2030 in a region which has a high installed hydropower capacity and proposes solutions to the problems of water abandonment and supply-demand imbalance. This is done by developing various models and pathways to meet the electricity, industry, and transportation energy demands in Sichuan Province, China within the confinement of the government policies. Hence, three different scenarios including reference scenarios, policy scenarios, and optimization scenarios are modeled. These scenarios consider the resource development potential of renewable energy, energy policies, and the development of advanced technologies. Under different hydropower generation capacities, hybrid hydropower-photovoltaic-wind-biomass energy systems are constructed using the EnergyPLAN model, and the planning models for a clean/zero-carbon energy system in 2030 are proposed. Results from the analysis of the models showed that the conservative policy models could reduce CO2 emissions to some extent. Decarbonization models with different levels of hydropower generation under different scenarios could all result in zero CO2 emissions. The large-scale use of energy storage results in a significant increase in investment costs, but a significant reduction in energy costs. The results of this study validate the possibility of achieving decarbonization in areas with high hydropower potential. This also suggests the best decarbonization model for meeting the different needs of the future energy system. This article provides a reference and basis for any province or region to achieve long-term decarbonization using hydropower.